Manuscript and Print Media Differences Shapers of the 1470s (Proto) Fairy Tales Cirino d’Ancona’s Liombruno and Vindalino da Spira’s Lionbruno - B. Bottigheimer, Ruth (Literartes, 2020)
This special issue of Literartes is devoted to fairy tales in different media. I have contributed the following miniature account of a European proto-fairy tale, which appeared in two competing media, a 1470 hand-produced manuscript and a 1476 machine-made printed booklet. The manuscript medium had a limited reach in its audience; the printed booklet, one of a quondam print run of many hundred, needed to incorporate the expectations of a much larger population in order to be saleable. Thus, it happened that the same plot, when produced in two different media in the 1470s, tells a different story with respect to God, money, and women.